Development and psychometric properties of a self-regulation scale about leisure time physical activity in Iranian male adolescents - Mohammad Hadi Abasi; Ahmad Ali Eslami; Fatemeh Rakhshani; Mansoor Shiri (Wolters Kluwer Medknow Publications, 2016)
Background: Self-regulation is one of the current psychological concepts that have been known as a determinant of leisure time physical activity. Due to cultural and social diversity in different societies and age groups, application of specific questionnaires is essential to perform investigations about physical activities. The aim of this study is development and evaluation of psychometric properties of a self-regulation questionnaire about leisure time physical activity in Iranian male adolescents. Materials and Methods: This cross-sectional study was conducted in 2013, and data of 603 male students from 12 high schools in Isfahan were collected. A comprehensive literature review and similar questionnaire review were conducted and 25 items were selected or developed to measure self-regulation. Comprehensibility of items was evaluated in a pilot study and an expert panel evaluated face and content validity. Exploratory factors analysis (EFA) was used for evaluation of construct validity and extraction of sub-constructs of self-regulation. Leisure time physical activity was assessed using International Physical Activity Questionnaire (IPAQ). Results: The mean age of the participants was 16.3 years (SD =1.0) and the range was 15-19 years. Cronbach's α coefficient of the questionnaire in the pilot and main study was 0.84 and 0.90, respectively. EFA resulted in four sub-constructs including "enlistment of social support," "goal setting," "self-construction," and "self-monitoring," which explained 63.6% of the variance of self-regulation. Conclusions: Results of this investigation provide some support to the validity and reliability of the 16-item questionnaire of self-regulation abut leisure time physical activity in the target group.